Horta compartilhada: Aplica????o de criptomoeda Iota em internet das coisas - Economia das coisas - Teixeira , F??bio Carli Rodrigues (2021)
Using a scenario of an urban community vegetable garden, this work presents the application of the Internet of Things in a case of Shared Economy, making use of the IOTA cryptocurrency and its distributed ledger technology, the Tangle, in order to control the functionalities of the vegetable garden, its payments, product distribution, and monitoring of vegetable development, based on the availability of a balance in a digital wallet associated with the vegetable garden control code. The vegetable garden can be accommodated in a building, garage and even in a vacant lot, in order to optimize and scale the use of resources used and products offered. Urban and peri-urban agriculture is identified by the UN as one of the solutions for food security and socioeconomic problems in poor communities. This work also discusses the improvements that the use of technologies and new forms of administration can bring to the national agricultural scenario. Another important discussion necessary for the legal use of digital currency is its state regulation, which is also covered in this work. The characteristics of the main cryptocurrencies that use Blockchain and IOTA are also presented, justifying the choice of the latter in the application of the vegetable garden. Finally, the results of the experiment carried out are presented and discussed, proving that the proposal is viable for use and can be easily adapted to the particularities of each community.